Hemophagocytic syndrome after living donor liver transplantation: a case report with a review of the literature - Norifumi Iseda; Tomoharu Yoshizumi; Takeo Toshima; Akinari Morinaga; Takahiro Tomiyama; Junichi Takahashi; Takashi Motomura; Yohei Mano; Shinji Itoh; Noboru Harada; Toru Ikegami; Yuji Soejima (Surgical Case Reports)
Abstract Background Hemophagocytic syndrome (HPS) is a rare and potentially fatal complication following liver transplantation. Case presentation A 63-year-old woman with decompensated liver cirrhosis secondary to hepatitis B virus infection underwent living donor liver transplantation using the right posterior section of her husband’s liver (graft volume, 581 g; 56.8% of the recipient’s standard liver volume). She developed small-for-size syndrome on postoperative day (POD) 7, and HPS was diagnosed on POD 12 by bone marrow aspiration (white blood cells, 300/μL; neutrophils, 30/μL). Given that she tested negative for viral (hepatitis B virus and cytomegalovirus) and bacterial infections, it was considered likely to be secondary HPS. Steroid pulse therapy was initiated, and her white blood cell count increased to 4290/μL on POD 15, indicating that her peripheral blood leukocytes had improved. There were no surgical complications, but the patient died of prolonged graft dysfunction with bacterial sepsis on POD 14. Conclusions We report a rare case of HPS occurring 2 weeks after living donor liver transplantation with a right posterior section graft, diagnosed early via bone marrow aspiration. This clinical course implies an association between HPS and graft dysfunction such as small-for-size syndrome. Further studies of the mechanism of hypercytokinemia-induced HPS are required to confirm the optimal treatment for HPS.